Successful Treatment of Neonatal Pylorospasm with Intravenous Atropine - Hyeong Jung Kim; Jeong Eun Shin; Jung Ho Han; Joo Hee Lim; Soon Min Lee; Min Soo Park; Kook In Park; Ran Namgung; Ho Seon Eun (Korean Society of Neonatology, 2019)
Pylorospasm is a cause of delayed gastric emptying in young infants. As in patients with hypertrophic pyloric stenosis, most pylorospasm patients present with projectile vomiting. However, unlike that in case of hypertrophic pyloric stenosis, no persistent pyloric stenotic lesions are present. As such, follow-up using serial gastrointestinal fluoroscopy or ultrasonography can be helpful in diagnosing patients with clinical signs of gastroparesis. Most cases can be treated conservatively, but some patients require pharmacologic treatment. Antispasmodics have been proposed as a treatment for pylorospasm, but their use in neonates and infants has rarely been reported. Herein, we present a case of pylorospasm diagnosed in the neonatal period and successfully treated with intravenous atropine.